Molten salt synthesis and optical properties of Eu3+, Dy3+ or Nd3+ doped NiNb2O6 columbite-type phosphors - BAŞAK, ALİ SADİ; ERDEM, MURAT (ELSEVIER SCI LTD, 2015)
Pure, Eu3+, Dy3+ or Nd3+-doped NiNb2O6 powders have been prepared by a molten salt synthesis method by using Li2SO4-Na2SO4 salt mixture as a flux at relatively low temperatures as compared to the solid state reaction method. X-ray diffraction patterns of pure NiNb2O6 samples indicated an orthorhombic single phase. For Eu3+-doped NiNb2O6 samples, the luminescence of Eu3+ was observed at 615 nm as red emission while Dy3+-doped NiNb2O6 showed yellow emission at 577 nm and Nd3+ doped sample exhibited a typical emission at 1064 nm varying with the Eu3+ or Nd3+ doping concentrations. These luminescence characteristics of the doped samples may be attributed to the energy transfer between rare earth ions and NiO6 octahedral groups in the columbite structure. (C) 2015 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Optical properties; Columbite niobate; Molten salt synthesis; PHASE; LUMINESCENCE; MORPHOLOGY; GROWTH